Impact of nutrient deficiency and harvesting strategy on biomass and phycocyanin production in Spirulina cultures - Lim, Hooi Ren; Khoo, Kuan Shiong; Show, Pau Loke (Frontiers in Bioengineering and Biotechnology, 2025)
Recent research has focused on issues related to contamination, nutrient availability, and strain selection, but there has been insufficient focus on harvesting research. This study employed an integrated continuous cultivation and harvesting strategy for a Spirulina microalgae biorefinery. The effects of nutrient-deficiency, harvesting ratio, and NaNO3 addition on biomass concentration and productivity and phycocyanin accumulation of Spirulina were investigated. The lowest biomass productivity of 0.015 g/L/day was observed in Spirulina cultivated in NaNO3 deficient medium. A harvesting ratio of 10% showed a consistent range of harvested dry biomass weight (0.20–0.22 g). Addition of 2.50 g/L NaNO3 resulted in a significant increase in C-phycocyanin (C-PC) and allophycocyanin (APC) concentration from 34.37 mg/g to 68.35 and 27.08 to 33.23 mg/g, respectively. Biomass productivity of 1-L and 10-L batch culture was found to be 0.23 g/L/d and 0.21 g/L/d, respectively. Both 1-L and 10-L batch cultures showed a significant increase in phycocyanin accumulation due to the addition of 2.50 g/L of NaNO3. These findings highlight the feasibility of continuous cultivation and optimized harvesting for scalable biomass and phycocyanin production, offering valuable insights for industrial biorefineries that seek to enhance microalgae-based bioactive compound extraction.